An exploratory analysis of the relations between the rate of physiological habituation, the acquired capability for suicide, and acute risk factors for suicide. Issue 3 (13th July 2015) - Smith, Phillip N; Wolford-Clevenger, Caitlin; Selwyn, Candice N; Poindexter, Erin; Lechner, William; Grant, DeMond M.; Cukrowicz, Kelly C
Abstract : Purpose: – The interpersonal theory of suicide proposes that an individual must acquire the capability for suicide to carry out a near-lethal or lethal suicide attempt. This capability develops via habituation in response to painful and provocative life events. Some individuals might be more vulnerable to developing the capability for suicide because they habituate more quickly to stimuli. The purpose of this paper is to examine the relations between the rate of physiological habituation and acquired capability, proxies for acquired capability, and acute risk factors for suicide. Design/methodology/approach: – Depressed, suicidal individuals completed self-report assessments and a startle reflex task assessing the rate or speed of physiological habituation in response to repeated bursts of white noise. Findings: – Slower habituation was associated with hopelessness and negative stressors. The rate of habituation was not associated with acquired capability. Originality/value: – The current study informs the understanding of how physiological habituation is related to suicide risk factors.